Analisis Competitive Profile Matrix (CPM) Pada KSPPS BMT Dana Mentari: Strategi Peningkatan Daya Saing dalam Ekonomi Syariah - Fariha, Zulfia Nur; Putri, Nadiya Berliana; Odilien, Rizka Ayu Okty; Shafrani, Yoiz Shofwa (FEB Universitas Maritim Semarang, 2025)
KSPPS BMT Dana Mentari Purwokerto faces tight competition with other cooperatives such as PNM Mekar Sudagaran Sidareja in supporting MSMEs through sharia financing. This study analyzes the competitive position of BMT Dana Mentari using the Competitive Profile Matrix (CPM) and formulates a sharia-based business strategy. A descriptive qualitative approach is applied with data from interviews (May 2025), observations, and documents (OJK, 2025). The CPM results show that BMT Dana Mentari has a score of 3.25, superior to PNM Mekar (3.05), with strengths in sharia compliance and personal service. The main weakness is digital technology. The proposed strategies include digitalization of mobile applications (2026) and development of musyarakah products, in accordance with the itsar principle. This study provides guidance for sharia cooperatives to increase the competitiveness and empowerment of MSMEs.